The Impact of Covid-19 on the Institutional Fabric of Higher Education Old Patterns, New Dynamics, and Changing Rules? - Pinheiro, Rómulo; Balbachevsky, Elizabeth; Pillay, Pundy; Yonezawa, Akiyoshi (Springer Nature, 2023)
This open access book assesses how the Covid-19 pandemic caught higher education systems throughout the world by surprise. It maps out the responses of higher education institutions to the challenges and strategic opportunities brought about by the pandemic, and examines the effects such responses may have. Bringing together scholars and case studies from Europe, Asia, Africa and the Americas, the book is both comparative and global in nature. It also brings together researchers from a variety of disciplinary fields, including political scientists, historians, economists, sociologist, and anthropologists. In doing so, the book fosters an inter-disciplinary dialogue and inclusive methodological approach for unpacking the complexities associated with modern higher education systems and institutions.